Potential strategies to prevent encrustations on urinary stents and catheters – thinking outside the box: a European network of multidisciplinary research to improve urinary stents (ENIUS) initiative. (3rd July 2021) - Abou-Hassan, Ali; Barros, Alexandre; Buchholz, Noor; Carugo, Dario; Clavica, Francesco; de Graaf, Petra; de La Cruz, Julia; Kram, Wolfgang; Mergulhao, Filipe; Reis, Rui L; Skovorodkin, Ilya; Soria, Federico; et al.
ABSTRACT: Introduction: Urinary stents have been around for the last 4 decades, urinary catheters even longer. They are associated with infections, encrustation, migration, and patient discomfort. Research efforts to improve them have shifted onto molecular and cellular levels. ENIUS brought together translational scientists to improve urinary implants and reduce morbidity. Methods & materials : A working group within the ENIUS network was tasked with assessing future research lines for the improvement of urinary implants. Topics were researched systematically using Embase and PubMed databases. Clinicaltrials.gov was consulted for ongoing trials. Areas covered: Relevant topics were coatings with antibodies, enzymes, biomimetics, bioactive nano-coats, antisense molecules, and engineered tissue. Further, pH sensors, biodegradable metals, bactericidal bacteriophages, nonpathogenic uropathogens, enhanced ureteric peristalsis, electrical charges, and ultrasound to prevent stent encrustations were addressed. Expert opinion: All research lines addressed in this paper seem viable and promising. Some of them have been around for decades but are yet to proceed to clinical application (i.e. tissue engineering). Others are very recent and, at least in urology, still only conceptual (i.e. antisense molecules). Perhaps the most important learning point resulting from this pan-European multidisciplinary effort is that collaboration between all stakeholders is not only fruitful but also truly essential.